STANDARDIZATION PROBLEMS OF MEDICINAL PREPARATIONS FROM RHODIOLA ROSEA L. - V. A. Kurkin; T. K. Ryazanova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
Rhodiola rosea L. rhizomes and roots are pharmacopoeial raw materials, which are used in official medicine for obtaining medicines with adaptogenic activity. One of the most common problems in the production of medicines from Rhodiola rosea L. rhizomes and roots is the use of poor quality medicinal plant materials, which leads to the absence of biologically significant compounds in the preparations. One of the possible reasons is the shortcomings in the existing approaches to the standardization of Rhodiola rosea L. raw materials and preparations.The aim of the study is the improvement of approaches to the standardization of medicinal preparations from Rhodiola rosea L. rhizomes and roots.Materials and methods. Experimental and industrial samples of liquid extract from Rhodiola rosea L. roots, as well as reference samples of rosavin and salidroside, were used as materials of the research. The HPLC analysis was carried out using a Milichrom-6 chromatograph (NPAO Nauchpribor) under the following conditions of reversed-phase chromatography in an isocratic mode: a steel column KAKH-6-80-4 (2 mm x 80 mm; Separon-C18 7 μm), a mobile phase - acetonitrile: 1% solution of acetic acid in water in the ratio of 14:86, the elution rate was 100 μL/min, the eluent volume was 2000 μL. The constituents were detected at the wavelength of 252 nm (rosavin) and 278 nm (salidroside).Results. An assay of rosavin and salidroside in the liquid extract of Rhodiola rosea L. was developed using the HPLC method. It was determined that the content of rosavin in the samples of the liquid extracts obtained from Rhodiola rosea L. rhizomes and roots of the pharmacopoeial quality, varied from 0.21%±0.03% to 0.32%±0.04%, salidroside - from 1.13% ±0.05% to 2.71%±0.12%, respectively. The results of statistical processing indicate that the relative error of the average result for the determination of rosavin and salidroside in the preparations of Rhodiola rosea L. with a confidence level of 95% does not exceed ±6.0%.Conclusion. Thus, methodological approaches to the analysis of medicinal preparations from Rhodiola rosea L. rhizomes and roots have been substantiated. These methodological approaches consist of the quantitative determination of the dominant and diagnostically significant biologically active compounds - rosavin and salidroside.